Navigating Organisational Challenges in the Journey of BI-Driven Digital Transformations - Hwang, Yoo Jin (Auckland University of Technology, 2025)
Business Intelligence-driven Digital Transformation (BI-driven DT) has proven to enhance performance and drive operational excellence across industries. However, despite its clear benefits, organisations encounter numerous challenges in implementing and sustaining these initiatives effectively. Earlier research highlighted that organisational factors often outweigh technological aspects in determining successful outcomes. Recent research continues to reinforce this perspective, emphasising that the challenges faced in BI-driven DT are deeply influenced by organisational dynamics. This study aims to provide a comprehensive understanding of how organisational factors contribute to these challenges and proposes a framework integrating theoretical and empirical findings to guide successful BI-driven DT. Drawing on a systematic literature review (SLR) and a case study of a real-world BI-driven DT project, the research identifies the organisational factors and challenges related to BI-driven DT. Top Management Support, Clear Vision & Strategy, Data-Driven Innovation & Agility, and Roles & Skills are identified as the key organisational factors that impact BI-driven DT. These factors demonstrate interrelationships with recurring challenges like Resistance to Change, Strategic Misalignment, and Skill Gaps & Training Deficiencies. Also, the research highlights Interdepartmental Collaboration as a significant applied construct that is often underexplored in academic writing and appears less prominent in the literature. These insights reveal variations between theoretical constructs and real-world contexts, underscoring the importance of tailoring strategies to specific organisational environments. The study proposes a framework that identifies key organisational factors and maps their relationships to recurring challenges, which serves as a diagnostic tool for identifying organisational weaknesses and a strategic guide for addressing challenges. This framework enhances theoretical understanding and offers actionable guidance for practitioners. It is particularly useful for organisational leaders, project managers, and decision-makers seeking applicable strategies for BI-driven DT. Furthermore, insights derived from single-industry, such as finance and SME-specific perspectives, enable the development of targeted strategies, addressing the unique challenges within different organisational contexts. By integrating theoretical and empirical data, the study contributes to academic literature while equipping organisations with practical tools to navigate the complexities of BI-driven DT effectively.